Perbandingan Pemberian Air Kelapa Dengan Jahe Merah Pada Ibu Hamil Trimester I Dalam Menurunkan Hiperemisis Gravidarum Di BPM Umiatin - Umiatin Umiatin; Ita Herawati (Malahayati Nursing Journal, 2022)
ABSTRACT According to WHO, the incidence of hyperemesis gravidarum reaches 12.5% of all pregnancies in the world. Pregnancy check-up visits for pregnant women in Indonesia obtained data on mothers with hyperemesis gravidarum reaching 14.8% of all pregnancies. Nausea and vomiting occur in 60-80% of primigravida and 40-60% of multigravida. Management of nausea and vomiting can be done by non-pharmacological methods. Non-pharmacological therapies such as drinking boiled red ginger and coconut water. Red ginger contains zingiberol, zingiberena essential oil, curcumin, bisabilena, flandrena, gingerol, and vitamin A which can reduce nausea and vomiting. Coconut water also contains minerals, namely magnesium, potassium, and calcium. It turns out that drinking coconut water can relieve symptoms of nausea and vomiting. It is known that the comparison of giving coconut water with red ginger to pregnant women in the first trimester in reducing hyperemia gravidarum. Quasi experimental with a pretest protest design with a two experimental design. The samples in this study were all pregnant women in the first trimester at BPM Umiatin in January - February 2022 as many as 60 people, the sampling technique was total sampling. There is an effectiveness of giving coconut water and red ginger to pregnant women in the first trimester in reducing hyperemia gravidarum (p.value 0.000). After comparison between the groups of giving coconut water and red ginger decoction, it was concluded that both administrations were equally effective in reducing hyperemia gravidarum. Coconut water and red ginger decoction are both effective in reducing hyperemia gravidarum. Midwives are expected to provide counseling to pregnant women how to make red ginger stew and drink coconut water to reduce hyperemesis gravidarum. Keywords : Hyperemesis Gravidarum, Coconut Water, Red Ginger ABSTRAK Menurut WHO jumlah kejadian hiperemesis gravidarum mencapai 12,5% dari seluruh jumlah kehamilan di dunia. Kunjungan pemeriksaan kehamilan ibu hamil di Indonesia diperoleh data ibu dengan hiperemesis gravidarum mencapai 14,8% dari seluruh kehamilan. Mual dan muntah terjadi pada 60-80% primigravida dan 40-60% pada multigravida. Penatalaksanaan mual dan muntah dapat dilakukan dengan cara non farmakologi. Terapi nonfarmakologis seperti minum rebusan jahe merah dan air kelapa. Jahe merah mengandung zingiberol, minyak atsiri zingiberena, kurkumen, bisabilena, flandrena, gingerol, vitamin A yang bisa menurunkan mual muntah. Air kelapa juga memiliki kandungan mineral, yaitu magnesium, kalium, dan kalsium yang ternyata minum air kelapa dapat meredakan gejala mual muntah. Diketahui perbandingan pemberian air kelapa dengan jahe merah pada ibu hamil trimester I dalam menurunkan hiperemisis gravidarum. Quasi eksperimental dengan rancangan pretest protest with design two eksperiment. Sampel dalam penelitian ini adalah seluruh ibu hamil trimester I di BPM Umiatin pada bulan Januari - Februari 2022 sebanyak 60 orang, teknik pemgambilan sampel yaitu total sampling. Ada efektivitas pemberian air kelapa dan jahe merah pada ibu hamil trimester I dalam menurunkan hiperemisis gravidarum  (p.value 0,000). Perbandingan sesudah antara kelompok pemberian air kelapa dan rebusan jahe merah disimpulkan bahwa dari kedua pemberian sama-sama efektif dalam menurunkan hiperemisis gravidarum. Air kelapa dan rebusan jahe merah sama-sama efektif dalam menurunkan hiperemisis gravidarum. Diharapkan Bidan memberikan konseling kepada ibu hamil cara membuat rebusan jahe merah dan minum air kelapa untuk mengurangi hiperemesis gravidarum. Kata Kunci: Hiperemesis Gravidarum, Air Kelapa, Jahe Merah